The Effect Of Marketing Personalization And Customer Trust On Customer Loyalty At Gojek Indonesia - Tanjung, Ummu Salmah; Rini, Endang Sulistya; Fadli, Fadli (DAS CONFERENCE INTERNATIONAL SERIES, 2026)
This study aims to analyze the influence of marketing personalization and customer trust on customer loyalty on the Gojek Indonesia platform. Competition in the ride-hailing and super-app industries in Indonesia is increasingly fierce, making customer loyalty a critical factor for business success. The research method used is quantitative with a survey approach. The research sample consisted of 150 active Gojek user respondents in Medan City selected through a purposive sampling technique. Data were collected using a structured questionnaire based on a 5-point Likert scale and analyzed using multiple linear regression analysis with the help of SPSS 26 software. The results showed that marketing personalization had a positive and significant effect on customer loyalty (β = 0.412; p < 0.05), customer trust had a positive and significant effect on customer loyalty (β = 0.387; p < 0.05), and both variables simultaneously influenced customer loyalty with an R² value of 0.631. These findings indicate that an appropriate marketing personalization strategy and strengthening customer trust are determinants in building customer loyalty in the digital ecosystem.